2017
DOI: 10.1039/c6py01076h
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus-responsive non-ionic diblock copolymers: protonation of a tertiary amine end-group induces vesicle-to-worm or vesicle-to-sphere transitions

Abstract: Morpholine-functionalised poly(glycerol monomethacrylate)-poly(2-hydroxypropyl methacrylate) diblock copolymer vesicles are transformed into worms or spheres on lowering the solution pH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 71 publications
(94 reference statements)
1
54
1
3
Order By: Relevance
“…End-group ionisation effects have been recently reported for various aqueous PISA formulations by Lovett and coworkers 43,44 and Penfold et al 45,46 In each case, ionisation (or protonation) of a terminal carboxylic acid (or tertiary amine) group led to a change in the diblock copolymer morphology owing to greater solvation of the steric stabiliser block, which leads to a subtle shift in the fractional packing parameter. In contrast, we show herein that end-group ionisation is an essential prerequisite to ensure colloidal stability when using PNMEP as a moderately hydrophilic steric stabiliser block.…”
Section: Resultsmentioning
confidence: 92%
“…End-group ionisation effects have been recently reported for various aqueous PISA formulations by Lovett and coworkers 43,44 and Penfold et al 45,46 In each case, ionisation (or protonation) of a terminal carboxylic acid (or tertiary amine) group led to a change in the diblock copolymer morphology owing to greater solvation of the steric stabiliser block, which leads to a subtle shift in the fractional packing parameter. In contrast, we show herein that end-group ionisation is an essential prerequisite to ensure colloidal stability when using PNMEP as a moderately hydrophilic steric stabiliser block.…”
Section: Resultsmentioning
confidence: 92%
“…Variable‐temperature 1 H NMR analysis revealed that the degree of hydration of the PHPMA block varied with temperature, leading to a subtle alteration in the packing parameter and thus a morphological transition between worms and spheres. Later, a pH‐responsive mechanism based on ionization of a single end‐group, such as carboxylic acid or morpholine, to change the morphologies was reported. Ionization of a polymer end‐group with a minimum use of base or acid induced a sufficient change in the hydration degree of the PHPMA block and thus the packing parameter, leading to a pH‐responsive morphological transition.…”
Section: Raft Aqueous Dispersion Pisamentioning
confidence: 99%
“…Ionization of a polymer end‐group with a minimum use of base or acid induced a sufficient change in the hydration degree of the PHPMA block and thus the packing parameter, leading to a pH‐responsive morphological transition. On the basis of the primary thermally responsive behavior of PHPMA‐based nano‐objects, PGMA−PHPMA vesicles with pH‐responsive end‐groups were reported to exhibit complex stimulus‐responsive behavior, which critically depended on PHPMA DP, pH, and temperature …”
Section: Raft Aqueous Dispersion Pisamentioning
confidence: 99%
“…SCNPs can not only mimic the delicate controlled folding process of proteins with controlled size and morphology, [31][32][33] but can also self-assemble into more complexed 3D structures. 34 Furthermore stimuli-responsive polymeric nanoparticles, also called "smart" or "intelligent" nanoparticles that are capable of conformational and chemical changes by adapting the external stimuli 35,36 have increasingly attracted interest due to their diverse range of applications in delivery and release of drugs, 37,38 diagnostics, 39 sensors. 40 Dynamic covalent chemistry is a very suitable candidate for building intelligent materials which can be responsive to the environmental changes, such as pH or input stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…35,[55][56][57] The structures and properties of superparticles formed by self-assembled SCNPs have been proved to be entirely different from traditional block copolymer micelles. 58 Zhao et al 59 and Chen et al 58 reported the first examples of self-assembly and disassembly of diblock single chain Janus nanoparticles (SCJNPs).…”
mentioning
confidence: 99%